The Persecution and Murder of the European Jews by Nazi Germany, 1933-1945: Volume 1: German Reich 1933-1937 - Pearce, Caroline; Heim, Susanne; Gruner, Wolf (De Gruyter Oldenbourg, 2019)
Frontmatter -- Contents -- Foreword to the English Edition -- Editorial Preface -- Introduction -- List of Documents -- Documents: 1-106 -- Documents: 107-213 -- Documents: 214-320 -- Glossary -- Approximate Rank and Hierarchy Equivalents -- List of Abbreviations -- List of Archives, Sources, and Literature Cited -- Index